Cooling neonates who do not fulfil the standard cooling criteria – short‐ and long‐term outcomes. (29th September 2014) - Smit, Elisa; Liu, Xun; Jary, Sally; Cowan, Frances; Thoresen, Marianne
Abstract Aim Therapeutic hypothermia is effective and without serious adverse effects in term infants with hypoxic–ischaemic encephalopathy. It is unknown whether other neonatal patient groups could benefit from therapeutic hypothermia. Since 2006, our centre has offered cooling to infants fulfilling the standard cooling criteria, but also to those who did not. Methods Observational study with prospective data collection over a 6‐year period in a regional cooling centre. Complications and outcome were compared between infants who were cooled not fulfilling the standard inclusion and exclusion criteria as set out in the CoolCap/TOBY protocol (n = 36) and infants who fulfilled the standard entry criteria (n = 129). Results 21.8% of cooled infants did not fulfil standard cooling entry criteria. This included infants cooled >6 postnatal hours, late preterm infants, and infants with postnatal collapse, major cranial haemorrhage, congenital cardiac disease and surgical conditions. Complication rates and long‐term outcome did not differ significantly between the groups, apart from in infants with a major cranial haemorrhage, who had higher rates of coagulopathy and the worst outcome (80% death/disability). Conclusion Cooling can be considered for infants with neonatal encephalopathy following postnatal collapse or preterm birth, those with underlying surgical or cardiac conditions, and infants starting cooling >6 postnatal hours.